Uptake and use of recommendations for the diagnosis, severity scoring and management of chronic graft-versus-host disease: An international survey of the EBMT-NCI Chronic GVHD Task Force - Duarte, Rafael F. (2013)
In 2005, the NIH consensus conference published a series of papers recommending methods to improve the conduct of clinical trials in chronic graft-versus-host disease (GVHD). Although the NIH recommendations were primarily aimed at strengthening research, several papers addressed issues relevant for clinical practice, particularly diagnosis, severity scoring, and ancillary and supportive care practices. We conducted an international survey to assess the uptake of these recommendations, identify barriers to greater use, and document the use and perceived effectiveness of available treatments. The response rate for the American survey of 1,387 practitioners was 21.8%, and it was 24.6% for 407 centers surveyed in Europe, Asia, Australia and Africa. Most respondents were familiar with the NIH consensus recommendations (94-96%) and used them in practice. Multiple barriers to greater use were reported. Besides lack of time (55-62%), unfamiliarity with the recommendations, scarcity of evidence supporting the impact of recommendations on outcomes, insufficient training/experience in chronic GVHD management, and inaccessibility of subspecialists were also endorsed. Systemic corticosteroids were reported to be the most effective treatment for chronic GVHD, but many others were perceived to have moderate or great success. Therapeutic management of steroid-refractory chronic GVHD was identified as the highest priority for research.